Insight into the frequent occurrence of dura mater graft-associated Creutzfeldt-Jakob disease in Japan. Issue 10 (17th April 2013) - Hamaguchi, Tsuyoshi; Sakai, Kenji; Noguchi-Shinohara, Moeko; Nozaki, Ichiro; Takumi, Ichiro; Sanjo, Nobuo; Sadakane, Atsuko; Nakamura, Yosikazu; Kitamoto, Tetsuyuki; Saito, Nobuhito; Mizusawa, Hidehiro; Yamada, Masahito
Abstract : Objective: More than 60% of patients worldwide with Creutzfeldt-Jakob disease (CJD) associated with dura mater graft (dCJD) have been diagnosed in Japan. The remarkable frequency of dura mater grafts in Japan may possibly contribute to the elevated incidence of dCJD, but reasons for the disproportionate use of this procedure in Japan remain unclear. We investigated differences between dCJD patients in Japan and those elsewhere to help explain the more frequent use of cadaveric dura mater and the high incidence of dCJD in Japan. Methods: We obtained data on dCJD patients in Japan from the Japanese national CJD surveillance programme and on dCJD patients in other countries from the extant literature. We compared the demographic, clinical and pathological features of dCJD patients in Japan with those from other countries. Results: Data were obtained for 142 dCJD patients in Japan and 53 dCJD patients elsewhere. The medical conditions preceding dura mater graft transplantation were significantly different between Japan and other countries (p<0.001); in Japan, there were more cases of cerebrovascular disease and hemifacial spasm or trigeminal neuralgia. Patients with dCJD in Japan received dura mater graft more often for non-life-threatening conditions, such as meningioma, hemifacial spasm and trigeminal neuralgia, than in other countries. Conclusions: Differences in the medical conditions precipitating dura mater graft may contribute to the frequent use of cadaveric dura mater and the higher incidence of dCJD in Japan.